The effect of non-performance loan (npl) mediation and interest rate moderation on the effect of capital adequacy ratio (car) and bopo on return on assets (roa) in consumer finance companies listed on the idx for 2019-2021 - Murtini; Eka Desy Purnama; Rudolf Lumbantobing (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the effect of the interaction between CAR and BOPO on financial performance (ROA) which is influenced by NPL as a mediating variable and interest rates as a moderating variable. The data in this study uses quantitative data obtained from financial reports, IDX and BPS. Data analysis used multiple linear regression which was applied with SPSS 25 software. The population taken was 7 finance companies, especially in the consumer finance sector which were listed on the IDX for the 2019-2021 period. The test results from this study concluded that CAR, BOPO, and NPL had a negative and significant effect on ROA. CAR has no significant effect on NPL. Meanwhile BOPO has a positive significant influence on NPL. Furthermore, NPL is not significantly positive mediating the effect of CAR on ROA. Whereas in the effect of BOPO on ROA, NPL can mediate negatively and significantly. Then, for the interest rate as a moderating variable, it can significantly moderate the effect of CAR on ROA positively and the effect of NPL on ROA negatively. But on the effect of BOPO on ROA, interest rates moderate positively.